1998
DOI: 10.1063/1.368319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pressures on the crystallization process of an amorphous Fe73.5Cu1Nb3Si13.5B9 alloy

Abstract: Amorphous Fe73.5Cu1Nb3Si13.5B9 alloys, prepared by a melt-spinning technique, were annealed at a temperature of 823 K under pressures in the range of 1–5 GPa and ambient pressure. The high pressure experiments were carried out in a belt-type pressure apparatus. The microstructure of the annealed alloys has been investigated by x-ray diffraction, electron diffraction, and transmission electron microscopy. Experimental results show that the initial crystalline phase in these annealed alloys is α-Fe solid solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…21,22 Considering the pressure and temperature dependence of average grain size, we can see that the coercivity i H c is inversely correlated with the average grain size in this system, indicating that the more grain refinement the less coercivity. Similar behaviors have been observed in some soft magnetic nanocrystalline and multilayer materials , such as Fe-Cu-Nb-Si-B system 13,20 and TbDyFe+Zr/Nb multilayer film. Table I.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…21,22 Considering the pressure and temperature dependence of average grain size, we can see that the coercivity i H c is inversely correlated with the average grain size in this system, indicating that the more grain refinement the less coercivity. Similar behaviors have been observed in some soft magnetic nanocrystalline and multilayer materials , such as Fe-Cu-Nb-Si-B system 13,20 and TbDyFe+Zr/Nb multilayer film. Table I.…”
supporting
confidence: 56%
“…The activation volume ∆V * is normally positive for amorphous alloys. 20 the atomic diffusion coefficient D will decrease with the increase in pressure and the decrease in temperature, resulting in a lower crystal growth rate during the crystallization process. As a whole, the easy nucleation and lower growth rate together give rise to the grain refinement.…”
mentioning
confidence: 99%
“…Taking pressure (P) into account and assuming that the interfacial energy ( ) is independent of it, G * is given by [6][7][8][9] ∂( G * ) ∂P…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [6,7] reported that pressure affected the transformation behaviour of amorphous alloys significantly and often led to the formation of dense crystalline phase. Recently, we annealed amorphous Fe 86 Zr 7 B 6 Cu 1 ribbons by hot isothermal pressing (HIP) and found that a distinct improvement of the soft magnetic properties is induced by HIP [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…The crystalline volume fraction V cry is calculated from the XRD spectra according to [13] V cry ¼ I cry I cry þ I am ð1Þ…”
Section: Structural Analysismentioning
confidence: 99%